Graphene foam/carbon nanotube/poly(dimethyl siloxane) composites as excellent sound absorber. (November 2017) - Wu, Ying; Sun, Xinying; Wu, Wei; Liu, Xu; Lin, Xiuyi; Shen, Xi; Wang, Zhenyu; Li, Robert K.Y.; Yang, Zhiyu; Lau, Kin-Tak; Kim, Jang-Kyo
Abstract: The sound damping capabilities of graphene foam (GF)/carbon nanotube (CNT)/poly(dimethyl siloxane) (PDMS) composites to low-frequency sound waves are studied. To our best knowledge, this work reports for the first time the development of three dimensional graphene-based composites for sound absorption achieving a commercially viable absorption coefficient higher than 0.3 over a wide frequency range of 100–1000 Hz. Cellular GF is fabricated by template-directed chemical vapor deposition and the composites are prepared by infiltrating solvent-diluted PDMS with and without multi-walled CNTs (MWCNTs) into the porous structure of GF. The GF/PDMS composites with a porosity of 51.5% and a thickness of 1.6 mm are capable of shielding a maximum 70% of the incident sound waves at a low frequency between 100 and 200 Hz. This value is much better than the damping performance of commercial sound absorbing materials with much larger thicknesses. The incorporation of MWCNTs into the PDMS matrix allows the frequency band to be expanded to a wider range from 100 to 1000 Hz while achieving a uniform absorption of more than 30% of the incident sound waves. The outstanding sound damping capabilities of GF/PDMS and GF/CNT/PDMS composites make them excellent candidates for low-frequency noise shielding in many premises.